Early literacy in English as an additional language through Synthetic Phonics: A case study - Ferreira, Lucas Gabriel da Silva; Hitotuzi, Nilton (BELT - Brazilian English Language Teaching Journal, 2020)
The Synthetic Phonic Method (SPM) is often used in anglophone countries for the teaching of reading in the mother tongue. In other countries, data on the use of the SPM for teaching reading in an additional language reading are scarce. Thus, the study reported in this paper aimed to understand the literacy process in English as an additional language (EAL) of two Brazilian children through the SPM in an extension course offered at a federal university in the Amazon. Data were collected through audio and video recordings and interviews. Thematic Analysis was used for data analysis and interpretation. The results suggest that the SPM is effective for teaching Brazilian Portuguese-speaking children to read in English. The analysis also revealed some factors that influence pupils’ reading skills in EAL and their attitude towards the SPM, opening new possibilities for future studies in this area.